1988
DOI: 10.1002/nag.1610120507
|View full text |Cite
|
Sign up to set email alerts
|

Slope stability analyses for materials with a non‐linear failure envelope

Abstract: SUMMARYUpper bound techniques are used to analyse the stability of slopes of material failing according to a nonlinear failure criterion, such as closely jointed rocks. The global, extremal nature of upper bound calculations is discussed, as is the inverse use of such procedures for obtaining safe lower bound estimates for material strength properties in back analyses. Specific results are presented for the material model proposed by Hoek and Brown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 19 publications
3
42
1
1
Order By: Relevance
“…Several authors have suggested yield functions that take the ϕ-dependency of stress level into account, for example: De Mello [16], Charles and Watts [17], Collins et al [18], Simonini [19], Baker [20], and Baker and Awidat [21]. In the present study, it has been found appropriate to use an expression of the form:…”
Section: The Nonlinear Failure Envelopementioning
confidence: 94%
“…Several authors have suggested yield functions that take the ϕ-dependency of stress level into account, for example: De Mello [16], Charles and Watts [17], Collins et al [18], Simonini [19], Baker [20], and Baker and Awidat [21]. In the present study, it has been found appropriate to use an expression of the form:…”
Section: The Nonlinear Failure Envelopementioning
confidence: 94%
“…To solve this problem, Zhang and Chen [15] proposed a numerical method, which they called the inverse method. Other researchers have proposed methods based on a technique called the tangential technique [18]. Collins et al [18] generalized the work of Chen [1] on the stability of slopes which material's resistance is governed by a linear failure criterion to the case of nonlinear materials.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have proposed methods based on a technique called the tangential technique [18]. Collins et al [18] generalized the work of Chen [1] on the stability of slopes which material's resistance is governed by a linear failure criterion to the case of nonlinear materials. Instead of using Hoek-Brown's original criterion to evaluate the stability factor, they used a tangent Mohr-Coulomb criterion, characterized by a friction angle ϕ t and cohesion c t , and proposed the following expression of the stability factor:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations